Criminal Sanctions Against the Crime of Misuse of Methamphetamine Types of Narcotics for Yourself (Case Study of Supreme Court Decision Number 1986 K/Pid.sus/2020) - Chandra Priono Naibaho; Alpi Sahari; Ahmad Fauzi (International Journal Reglement & Society (IJRS), 2022)
In the Supreme Court's decision No. 1986 K/Pid.sus/2020 that the Defendant had frequently used methamphetamine and the Defendant had last used methamphetamine on Wednesday, August 14, 2019 at around 09.00 am at the Witness Herman Alias' parents house. Bolong in Enrekeng, Enrekeng Village, Ganra District, Soppeng Regency. This study aims to analyze the legal regulation of criminal sanctions against the crime of abuse of methamphetamine type of narcotics for oneself, the concept of two-way punishment for the misuse of methamphetamine types of narcotics for oneself and criminal sanctions for the misuse of methamphetamine for oneself based on the Supreme Court Decision Number 1986 K. /Pid.sus/2020. This research method uses normative research with data types consisting of primary legal materials, secondary legal materials and tertiary legal materials. Based on the results of this study, the abuse of shabu for oneself in the Supreme Court's decision Number 1986 K/Pid.sus/2020 the defendant was only given a prison sentence, there should be rehabilitation measures for the defendant. The prison sentence imposed by the judex juris is classified as light, the judex juris imposes a sentence on the defendant with a prison sentence of 1 (one) year and 6 (six) months, while at the first level and the appeal level in the aquo case, the defendant is sentenced to imprisonment for 3 (three) year. Article 27 paragraph (1) letter a explains that every narcotics abuser of class 1 shall be sentenced to a maximum imprisonment of 4 (four) years